Implementation of the Project Based Learning Model for Social Sciences Material on Harmony in Ecosystems in the Aspects of Creative Thinking Skills and Learning Outcomes V Grade Students - Zainuri, Indra Paksana; Ferina Agustini; Joko Sulianto (International Journal of Asian Education, 2025)
This study was conducted to address the low creativity and learning outcomes of students in the subject of harmony in ecosystems science and natural sciences through the application of the Project Based Learning (PjBL) learning model. This type of research is quantitative with a quasi-experimental pretest-posttest control group design. The study population included all students of SDN Demaan Jepara in the 2024/2025 academic year, with a purposive sampling sample consisting of grade V as the experiment (34 students) and grade VI as the control (24 students). The instrument consisted of a multiple-choice test of learning outcomes and an observation sheet of student creativity based on four indicators of creative thinking: fluency, flexibility, originality, and elaboration. Data were analyzed using a t-test to examine differences in learning effectiveness. The results showed that the experimental group using the PjBL model had a significant increase in creativity and learning outcomes compared to the control group, with a significance value <0.05. The conclusion of the study confirms that the PjBL model is effective as an innovative learning strategy to improve creative thinking skills and student learning outcomes in elementary schools on the subject of harmony in ecosystems science and natural sciences. Practical implications are suggested for teachers to optimize all stages of PjBL with appropriate facilitation to strengthen student involvement and mastery of the material.